Closed reduction and percutaneous pinning vs open reduction and internal fixation in pediatric lateral condylar humerus fractures displaced by > 4 mm: an observational cross-sectional study - Li-wei Xie (BMC, 2021)
Abstract Background Although open reduction and internal fixation (ORIF) is recommended for lateral condylar humerus fractures (LCHFs) displaced by > 4 mm, several studies have reported the use of closed reduction and percutaneous pinning (CRPP) to treat LCHFs with significant displacement. However, little is known about the clinical differences between these two surgical techniques. This study aimed to compare the therapeutic effects of CRPP and ORIF in treating LCHFs displaced by > 4 mm. Methods We retrospectively reviewed pediatric LCHFs displaced by > 4 mm treated with either CRPP or ORIF at our center from June 2019 to October 2020. Song and Milch fracture classifications were used. Variables such as age at injury, sex, side injured, fracture displacement, fracture type, operating time, postoperative treatment, and complications were compared between the two techniques. Results One hundred twenty LCHFs met inclusion criteria. There were 36 Milch type I and 84 type II LCHFs, and 69 Song stage 4 and 51 stage 5 LCHFs. CRPP was performed in 45 cases and ORIF in 75 cases. No differences were found in age, sex, side injured, preoperative displacement, postoperative displacement, and length of immobilization between the CRPP and ORIF groups. There was a difference between operation time and pin duration. The CRPP group had shorter operation times and pin duration, and required no additional operations to remove internal pins. The average follow-up duration was 13.9 months. All patients achieved fracture union, and no complications such as infection, nonunion, delayed union, osteonecrosis, fishtail deformity, cubitus varus or valgus, or pain were recorded during follow-up. Bone spurs, lateral prominences, and decreased carrying angle were common complications in all groups. No obvious cubitus varus was observed. Unaesthetic scars were only observed in the ORIF groups. No differences in range of motion or elbow function was found among the different therapies. Conclusions Both CRPP and ORIF can achieve satisfactory clinical outcomes in treating LCHFs displaced by > 4 mm. No differences were found in complications or prognoses between the two groups. However, CRPP shows some advantages over ORIF, like less invasive surgery, no obvious scarring, and no need for secondary surgery with anesthesia for pin removal.